2012
DOI: 10.1002/nur.21474
|View full text |Cite
|
Sign up to set email alerts
|

Patient turnover and the relationship between nurse staffing and patient outcomes

Abstract: High patient turnover (patient throughput generated by admissions, discharges, and transfers) contributes to increased demands and resources for care. We examined how the relationship between registered nurse (RN) staffing and failure-to-rescue (FTR) varied with patient turnover levels by analyzing quarterly data from the University HealthSystem Consortium. The data included 42 hospitals, representing 759 nursing units and about 1 million inpatients. Higher RN staffing was associated with lower FTR. When patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 37 publications
2
74
2
3
Order By: Relevance
“…Daha önce-ki çalışmalarda da benzer bulgular mevcuttur, yoğun bakım hekimi bulunan kliniklerde ortalama YBÜ yatış süresinin kısaldığı bildirilmiştir (17)(18)(19). Ayrıca kalış süresi kısa olan ünitelerde, hasta giriş-çıkışı daha fazla olduğundan hemşirelik iş yükünün belirgin olarak arttığı bildirilmektedir (20). DYBÜ'deki TISS-28 skorunun yüksek bulunmasının bir nedeni de hasta döngüsünün daha fazla olması nedeni ile olabilir.…”
Section: Discussionunclassified
“…Daha önce-ki çalışmalarda da benzer bulgular mevcuttur, yoğun bakım hekimi bulunan kliniklerde ortalama YBÜ yatış süresinin kısaldığı bildirilmiştir (17)(18)(19). Ayrıca kalış süresi kısa olan ünitelerde, hasta giriş-çıkışı daha fazla olduğundan hemşirelik iş yükünün belirgin olarak arttığı bildirilmektedir (20). DYBÜ'deki TISS-28 skorunun yüksek bulunmasının bir nedeni de hasta döngüsünün daha fazla olması nedeni ile olabilir.…”
Section: Discussionunclassified
“…Four studies showed significant associations between lower nurse staffing (RN or all nursing staff) and higher rates of death (Blegen et al, 2011, Needleman et al, 2011, Sales et al, 2008. Two studies showed significant associations between lower staffing and higher rates of failure to rescue (Park et al, 2012, Twigg et al, 2013. While results from other studies were not statistically significant (e.g.…”
Section: O U T C O M E S a S S O C I A T E D W I T H N U R S E S T A mentioning
confidence: 95%
“…Eight mostly weak studies gave no strong evidence of beneficial associations between nursing support worker staffing and patient safety. Studies found no association with mortality (Unruh et al, 2007), failure to rescue (Park et al, 2012), length of stay (Unruh et al, 2007), venous thromboembolism (Ibe et al, 2008), or missed care . However, higher assistant staffing was associated with higher rates of falls (Hart andDavis, 2011, Lake et al, 2010), pressure ulcers (Seago et al, 2006), readmission rates (Weiss et al, 2011), medication errors (Seago et al, 2006), use of physical restraints M a n u s c r i p t…”
Section: O U T C O M E S a S S O C I A T E D W I T H N U R S I N G A mentioning
confidence: 99%
“…Kalış süresi kısa olan ünitelerde, hasta giriş-çıkışı daha fazla olduğundan hemşirelik iş yükünün belirgin olarak arttığı bildirilmektedir (14). Bizim çalışmamızda yoğun bakımlar arasında yatış süreleri anlamlı olarak farklı olmasa da YBÜ-3 te diğer YBÜ'lere göre yoğun bakım yatış süre ortalaması yüksek bulundu.…”
Section: Discussionunclassified